Ethnobotanical knowledge and ethnomedicinal uses of plant resources by urban communities of Khyber Pakhtunkhwa, Pakistan: a novel urban ethnobotanical approach - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab; Sajid Ullah; M. Abdullah-Al-Wadud (Journal of Ethnobiology and Ethnomedicine)
Abstract Study Background Ethnobotanical knowledge of plants in rural and remote areas is more common in Pakistan than in urban areas. This study was carried out to find the indigenous knowledge of plants in anthropogenically disturbed urban areas of Khyber Pakhtunkhwa, Pakistan. Materials and methods Eight visits (Two per season) were carried out from March 2023 to March 2024. The semi- structured questionnaire was administered to informants and analyzed using informant consensus factor (ICF), use values (UV), fidelity level (FL%), average direct matrix ranking (ADMR), and Jaccard index (JI). Results A total of 138 plant species belonging to 54 families, Asteraceae with the highest number of plant species (14) were recorded from 101 informants. Herbs were the dominant plant species (75%) and leaves were the most used parts (43%). The ICF value of 0.97 indicated a high consensus among informants regarding the use of plants for kidney disorders. The highest UV value of 0.78 showed a maximum use of the plant for ear diseases. The highest FL% of 91.8 indicated the highest use of A. sativum for alopecia. For plant use in medicinal purposes, the ADMR ranking came in first. JI values showed that 73 plant species were common in all the three urban areas. Conclusions The study area was highly disturbed by anthropogenic activities. However, it still contains a rich diversity of plant resources. Furthermore, investigation is required for the conservation and utilization of plant resources, discovery of novel drugs and climate resilience for the welfare of mankind.